Antiviral activity of five Asian medicinal pant crude extracts against highly pathogenic H5N1 avian influenza virus - Sornpet, Benjaporn; Potha, Teerapong; Tragoolpua, Yingmanee; Pringproa, Kidsadagon (Asian Pacific journal of tropical medicine, 2017)
To study the antiviral properties of the five Asian medicinal plants against in vitro infection by the highly pathogenic avian influenza virus (H5N1). Crude extracts of Andrographis paniculata, Curcuma longa (C. longa), Gynostemma pentaphyllum, Kaempferia parviflora (K. parviflora), and Psidium guajava obtained by both water and ethanol extractions were investigated for their cytotoxicity in the Madin–Darby canine kidney cells. Thereafter, they were investigated in vitro for antiviral activity and cytokine response upon H5N1 virus infection. The results revealed that both water and ethanol extracts of all the five studied plants showed significant antiviral activity against H5N1 virus. Among these plants, C. longa and K. parviflora showed strong anti-H5N1 activity. Thus, they were selected for further studies on their cytokine response upon virus infection. It was found that ethanol and water crude extracts of C. longa and K. parviflora induced significant upregulation of TNF-α and IFN-β mRNA expressions, suggesting their roles in the inhibition of H5N1 virus replication. To the best of the authors' knowledge, this study is among the earliest reports to illustrate the antiviral property of these Asian medicinal plants against the highly pathogenic avian H5N1 influenza virus. The results of this study shed light on alternative therapeutic sources for treatment of H5N1 influenza virus infection in the future.